2014
DOI: 10.1111/jam.12524
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of conjugated linoleic acid by the linoleate isomerase complex in food-derived lactobacilli

Abstract: Aims To assess strains of lactobacilli for their capacity to produce functional fatty acid-conjugated linoleic acid. To assess the linoleate isomerase for CLA production in the most efficient CLA producer. Methods and Results In this study, strains of food-derived lactobacilli were cultured in media with linoleic acid and CLA production was assessed. Most of the selected strains produced CLA at different levels, with Lactobacillus plantarum ZS2058 being the most efficient CLA producer converting over 50% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 41 publications
2
59
0
3
Order By: Relevance
“…According to our previous results (Yang et al . ), three intermediates were produced during CLA production in Lact. plantarum ZS2058.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our previous results (Yang et al . ), three intermediates were produced during CLA production in Lact. plantarum ZS2058.…”
Section: Resultsmentioning
confidence: 99%
“…; Yang et al . ). Those results indicated that the mechanism for LA isomerization to CLA might be shared by different Lactobacillus species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fatty acids were derived to corresponding methyl esters with (trimethylsilyl)-diazomethane (Sigma) as described previously. 10,11 The FAMEs were extracted in hexane and loaded on an Rtx-wax column (30 m £ 0.25 mm £ 0.25 mm) using a gas chromatograph (GC2010 plus; Shimadzu, Japan) fitted with a QP2010 Ultra mass spectrometer. Injections of 1 ml were performed automatically at a split ratio of 10:1.…”
Section: Fat Extraction From Bacterial Supernatant Fluids and Pelletsmentioning
confidence: 99%
“…The temperature program was described previously. 10 The injector and detector were operated at 240 C. Electron energy of 70 eV and ion source temperature of 220 C were used. The percentage conversion to CLNA isomers was calculated by dividing the amount of CLNA present in the broth after inoculation/incubation with the amount of linolenic acid present in the spiked broth before incubation.…”
Section: Fat Extraction From Bacterial Supernatant Fluids and Pelletsmentioning
confidence: 99%